2020
DOI: 10.1021/acs.jpcc.9b12023
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorption-Driven Roughening of Hydrothermally Grown KTa1–xNbxO3 Nanoparticles

Abstract: The chemical and physical properties of nanoparticle surfaces have significant effects on their growth processes and the resulting morphology. Hydrothermally grown KNbO3, KTaO3, and KTa1–x Nb x O3 were studied to examine the complex relationships between surface composition, phase, chemistry, and energetics and how these may be used to model and thereby control nanoparticle growth mechanisms. Two different composition-dependent growth modes were identified, where one type formed smooth surface facets, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Significant morphology changes corresponding to increasing KF/KOH concentrations were also observed. The nanocuboids shown in Figure were typical of particles grown at lower KF/KOH concentrations, and their morphologies matched the nucleation and growth via surface terraces behavior studied previously. , In contrast to the nanocuboids, anisotropically shaped particles also formed at higher concentrations of KF (KF/KOH > 0.20). These particles were flat rectangular flakes on the order of several hundred nanometers wide and ∼100 nm thick (Figure ), and EDS maps of these particles shown in Figure S1 did not demonstrate any significant composition segregation as the cuboidal KTN particles did.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Significant morphology changes corresponding to increasing KF/KOH concentrations were also observed. The nanocuboids shown in Figure were typical of particles grown at lower KF/KOH concentrations, and their morphologies matched the nucleation and growth via surface terraces behavior studied previously. , In contrast to the nanocuboids, anisotropically shaped particles also formed at higher concentrations of KF (KF/KOH > 0.20). These particles were flat rectangular flakes on the order of several hundred nanometers wide and ∼100 nm thick (Figure ), and EDS maps of these particles shown in Figure S1 did not demonstrate any significant composition segregation as the cuboidal KTN particles did.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the composition gradient could be inverted from having a tantalum-rich interior and a niobium-rich surface to a niobium-rich interior and a tantalum-rich surface by predissolving niobium oxide in a basic KOH solution before hydrothermal synthesis. 16 However, the same niobium oxide dissolution procedure could not be replicated with tantalum oxide. The inverted Ta−Nb composition gradient effect was mirrored here by the addition of high concentrations of KF (Figure 2), which implied that the KF, or more specifically the fluoride, similarly affected the dissolution of the oxides in solution.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations